Ultradian metabolic rhythm in the diazotrophic cyanobacterium Cyanothece sp. ATCC 51142 - Červený, Jan; Sinetova, Maria A; Valledor, Luis; Sherman, Louis A; Nedbal, Ladislav (Proceedings of the National Academy of Sciences of the United States of America, 2013)
The unicellular cyanobacterium Cyanothece sp. American Type Culture Collection (ATCC) 51142 is capable of performing oxygenic photosynthesis during the day and microoxic nitrogen fixation at night. These mutually exclusive processes are possible only by temporal separation by circadian clock or another cellular program. We report identification of a temperature-dependent ultradian metabolic rhythm that controls the alternating oxygenic and microoxic processes of Cyanothece sp. ATCC 51142 under continuous high irradiance and in high CO2 concentration. During the oxygenic photosynthesis phase, nitrate deficiency limited protein synthesis and CO2 assimilation was directed toward glycogen synthesis. The carbohydrate accumulation reduced overexcitation of the photosynthetic reactions until a respiration burst initiated a transition to microoxic N2 fixation. In contrast to the circadian clock, this ultradian period is strongly temperature-dependent: 17 h at 27 °C, which continuously decreased to 10 h at 39 °C. The cycle was expressed by an oscillatory modulation of net O2 evolution, CO2 uptake, pH, fluorescence emission, glycogen content, cell division, and culture optical density. The corresponding ultradian modulation was also observed in the transcription of nitrogenase-related nifB and nifH genes and in nitrogenase activities. We propose that the control by the newly identified metabolic cycle adds another rhythmic component to the circadian clock that reflects the true metabolic state depending on the actual temperature, irradiance, and CO2 availability.
Keywords: Photosynthesis; cirkadiánní rytmus; Nitrogen Fixation; Glycogen; cyanobacteria; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; bakteriální proteiny; regulace genové exprese u bakterií; Circadian Rhythm; oxidoreduktasy; Gene Expression Regulation, Developmental; Oxygen; kyslík; diurnal; Carbon Dioxide; metabolism; Hydrogen-Ion Concentration; Gene Expression Regulation, Bacterial; Bacterial Proteins; oxid uhličitý; Bioreactors; Cyanothece; vývojová regulace genové exprese; koncentrace vodíkových iontů; fotosyntéza; bioreaktory; Oxidoreductases; glykogen; fixace dusíku; oscillation